Reduced splenic uptake on 68Ga-Pentixafor-PET/CT imaging in multiple myeloma: a potential imaging biomarker for disease prognosis - Kraus, Sabrina; Klassen, Philipp; Kircher, Malte; Dierks, Alexander; Habringer, Stefan; Gaeble, Alexander; Kortuem, Klaus Martin; Weinhold, Niels; Ademaj-Kospiri, Valeeza; Werner, Rudolf A.; Schirbel, Andreas; Buck, Andreas K.; et al. (Theranostics, 2022)
Beyond being a key factor for tumor growth and metastasis in human cancer, C-X-C motif chemokine receptor 4 (CXCR4) is also highly expressed by a number of immune cells, allowing for non-invasive read-out of inflammatory activity. With two recent studies reporting on prognostic implications of the spleen signal in diffusion-weighted magnetic resonance imaging in patients with plasma cell dyscrasias, the aim of this study was to correlate splenic Ga-68-Pentixafor uptake in multiple myeloma (MM) with clinical parameters and to evaluate its prognostic impact. Methods: Eighty-seven MM patients underwent molecular imaging with Ga-68-Pentixafor-PET/CT. Splenic CXCR4 expression was semi-quantitatively assessed by peak standardized uptake values (SUVpeak) and corresponding spleen-to-bloodpool ratios (TBR) and correlated with clinical and prognostic features as well as survival parameters. Results: Ga-68-Pentixafor-PET/CT was visually positive in all MM patients with markedly heterogeneous tracer uptake in the spleen. CXCR4 expression determined by Ga-68-Pentixafor-PET/CT corresponded with advanced disease and was inversely associated with the number of previous treatment lines as compared to controls or untreated smouldering multiple myeloma patients (SUV(peak)Spleen 4.06 +/- 1.43 vs. 6.02 +/- 1.16 vs. 7.33 +/- 1.40; P < 0.001). Moreover, reduced splenic Ga-68-Pentixafor uptake was linked to unfavorable clinical outcome. Patients with a low SUV(peak)Spleen (<3.35) experienced a significantly shorter overall survival of 5 months as compared to 62 months in patients with a high SUV(peak)Spleen >5.79 (P < 0.001). Multivariate Cox analysis confirmed SUV(peak)Spleen as an independent predictor of survival (HR 0.75; P = 0.009). Conclusion: These data suggest that splenic Ga-68-Pentixafor uptake might provide prognostic information in pre-treated MM patients similar to what was reported for diffusion-weighted magnetic resonance imaging. Further research to elucidate the underlying biologic implications is warranted.